The Influence of Current Ratio, Leverage, Return on Total Assets, and Company Size on Bonds Rating (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this study is to find out the influence of Current Ratio, Leverage, Return on Total Assets, and Company on Bonds Rating in non-financial service industry sector listed on the Indonesia Stock Exchange. This research is uses secondary data from the Indonesia Stock Exchange listed company and list of companies that had been rated by PT Pefindo in 2014-2018. While the sampling method selection uses purposive sampling and the results are 15 non-financial service companies. The regression model is using an ordered logistic regression by IBM SPSS 23 version software. The research result shows that Current Ratio, Return on Total Assets, and Company Size partially have a significant influence on Bonds Rating. While Leverage has no significant influence on Bonds Rating.